Optimal sizing of distributed generation using firefly algorithm and loss sensitivity for voltage stability improvement - Zulkiffli Bin Abdul Hamid; Sylvester Jipinus; Ismail Musirin; Muhammad Murtadha Othman; Rahmatul Hidayah Salimin (Institute of Advanced Engineering and Science, 2020)
This paper proposes an optimization technique for distributed generation (DG) sizing in power system. The DG placement was done through Loss Sensitive (LS) technique to determine the suitable locations. The LS index is calculated such that the change in power losses is divided with generation increment and a rank of buses is obtained to identify the suitable locations for DG placement. Subsequently, a meta-heuristic algorithm, known as Firefly Algorithm (FA) was run to obtain the optimal size or capacity of the DG. The installation takes into consideration the aspect of voltage stability in terms of total real power losses and voltage profiles to be improved in the distribution system. Based on the experiment, the real power losses and voltage profiles were improved significantly as a result of the DG placement. In addition, the installation could prevent the power system from collapse as the reactive loading was increased to maximum.